PENGARUH KODE ETIK TERHADAP KINERJA KEUANGAN PERUSAHAAN (THE EFFECT OF CODE OF ETHICS ON FINANCIAL PERFORMANCE) - Riani Sukma Wijaya (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2018)
This study aims to examine empirically the effect of the code of ethics on the financial performance of the company. To determine corporate value, this research uses CV-Index. The indicator variables used are accountability, persistence, excellence, fairness, honesty, honor, respect, trust, integrity and responsibility. After determining the value of the code of ethics, then tested its influence on the financial performance of the company. Company's financial performance is determined by Market-to-book equity. The value of market-tobook equity is determined by SIZE, LEV, ROA, CV, H1 small and H1large. The data used in this study is secondary data in the form of annual financial statements of companies listed on the Stock Exchange. The analytical tool used to test the hypothesis is the OLS Regression. The test results show that there is no effect of code of ethics on the financial performance of the company. This study provides important implications for companies to express corporate values in the code of ethics.Keywords: CV-Index, code of athics, SIZE, ROA, LEV, Financial Performance